حضور أفكار ابن خلدون وتوينبي في تفسير مالك بن نبي للحركة الدورية للحضارة: The Presence of Ibn Khaldun and Toynbee’s Ideas in Malek Bennabi’s Interpretation of the Cyclical Movement of Civilization - Benlahcene , Badrane (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The research analysed the presence of the ideas of Ibn Khaldun and Toynbee in the thought of Malek Bennabi in his interpretation of the cyclical movement of civilization and its related issues. To achieve this goal, this study discussed the contributions of the cyclical school to the study of civilization, and then the presence of Ibn Khaldun’s and Toynbee’s ideas in Bennabi’s thought, in order to understand the epistemological link between them and Bennabi in terms of their influence upon him and his criticism of their ideas. The study relied on the descriptive analytical approach of the writings of Ibn Khaldun, Toynbee, and Bennabi with regard to the interpretation of the movement of civilization. The study concluded that Bennabi was familiar with their interpretations of civilization and relied on them in building his explanatory model and that the close link between Bennabi’s interpretation of the movement of civilization and what Ibn Khaldun and Toynbee accomplished makes them form one school. The study proved the importance of knowing the sources from which Bennabi drew his ideas and built his perspective in the study of civilization, in order to gain an in-depth understanding of his efforts.